Estandarización del proceso de elaboración de snacks tipo chips (papas y chifles) para la microempresa perteneciente a la Asociación de no videntes y baja visión de Cotopaxi (ANOVIC). - Enríquez García, Evelyn Raquel (2024)
The current research had as a main objective to establish the standardization of the production process of snacks based on potatoes and green bananas. The study of variables and analysis was implemented to establish the best process for making snacks in the microenterprise belonging to the association of the blind and low vision of Cotopaxi (ANOVIC). The association has appropriate machinery to carry out the snack production process. To standardize the process, preliminary tests were carried out to establish the study variables. For the potato snack the type of super chola potato was used and as a variable; two types of oil, two frying temperatures (170 °C-180 °C) and two frying times (3 min-4 min) and for the snack based on green banana; two varieties of green banana, two types of oil and two frying temperatures (170 °C-180 °C) were used as variables, resulting in 8 different treatments for each type of snack. To determine the best treatments, a sensory analysis was carried out with a completely randomized experimental statistical design (DCA) in the Infostat application. According to the results obtained, the best treatment in the potato-based snack was T 3 with the type of vegetable oil (soybean oil with omega 3 and palm olein), frying time (3 minutes) and frying temperature (170 ° C-180°C). The best treatment for the green banana-based snack was T 2 with the type of vegetable oil (soybean oil with omega 3 and palm olein), type of green banana (maqueño) and temperature (170 °C-180 °C). The following physicochemical analyzes were carried out on the best treatments: Humidity (potato 2.91% and chifle 1.68%), fat (potato 37.70% and chifles 37.01%) and peroxide index (potato 0.00 meqO 2 /kg and 0.00 meqO 2 /kg chifles) and microbiological analysis: count of mesophilic aerobes (10 CFU/g potato and <10 CFU/g chifle), molds (10 CFU/g potato and <10 CFU/g chifle), yeasts (<10 CFU/g potato and <10 CFU/g chifle) and Escherichia coli (<10 CFU/g potato and <10 CFU/g chifle). The values obtained adjust to the parameters established in the NTE INEN 2561:2010 standard. The production capacity was determined according to the current conditions of the enterprise (presence of existing machinery and infrastructure). A brief technical-economic study was carried out considering a production of 60% potato snacks and 40% green banana snacks, obtaining a break-even point of 49.55%. A comparison was made considering a 100% production of snack based on green bananas and a balance point of 23.05% was obtained. It is also evident that the venture has possibilities of being sustainable over time with both types of snacks.